Komoditi dan Konsumsi Benda Najis dalam Islam - Rohmadi Rohmadi (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2015)
In fulfillment of life , people try to find commodities that before not consumed into something consumable . Among the commodities for consume were from impure product itself . In Islamic studies remains, its allowed to consume processed mixed impure. Halal commodity are halal of the material , the way of processing, the process and storage presentation.